PIGMENTOS VERDES (CoXZn1-XO): PREPARAÇÃO, CARACTERIZAÇÃO E PROPRIEDADE REFLETIVA DE RADIAÇÃO NIR - Primo, Julia de Oliveira (2018)
This work aimed to synthesize white pigments of zinc oxide (ZnO) and green pigments of cobalt-doped zinc oxide (CoxZn1-xO), which were applied as reflective pigments of NIR radiation. The pigments were prepared from the aqueous emulsion of starch and zinc nitrate. To obtain white pigments, 400 mL aliquots were removed and calcined at different temperatures (600°C, 800°C and 1000°C). While, to obtain the green pigments, three factors were considered: temperature, precursor salt and percentage of dopant. To evaluate the temperature factor, from the addition of cobalt nitrate (10% m/ m) in the starch-zinc emulsion, fractions were calcined at temperatures of 600°C, 800°C and 1000°C, designated N. Co600; N.Co800 and N.Co1000. For the precursor salt factor, the acetate and cobalt chloride salts were used, in the proportion of 10% of the doping metal in the zinc-starch matrix, calcined at 1000 ° C, and named A.Co1000 and C.Co1000. In order to verify the influence of the percentage of dopant on the final properties of the pigments, pigments with 20 and 40% cobalt ion (nitrate salt) were prepared in the starch-zinc matrix, calcined at 1000°C, the pigments were named N.Co20 and N. Co40. The white and green pigments were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray fluorescence (FRX), Raman spectroscopy, B.E.T method and electron reflectance spectroscopy (UV-Vis). Its reflective properties were evaluated by NIR spectroscopy and the colorimetric parameters by the CIEL*a*b (1976) method. The white pigments are presented as monophasic, wurtzite hexagonal phase. The greens have the wurtzite phase as the majority, with the presence of a second phase for the pigment obtained at 600 ºC, and for those with a higher percentage of cobalt. All the pigments (white and green) presented high crystallinity, greater than to 80%. Texturally the pigments from the nitrate and chloride salts were classified as mesoporous; and those of acetate salt were classified as non-porous. The SEM images showed the presence of irregular clusters for the white pigments, and for the green pigments there is no significant difference when compared to the white pigments. As for the reflective properties of green pigments, they showed high reflectivity of NIR radiation, reaching R% greater than 50% for the pigments obtained at higher temperature and painting dispersed. In this way it is possible to use the pigments synthesized in NIR radiation reflective coatings, with the purpose of improving the thermal comfort inside the buildings.